Potentially important periods of change in the development of social and role functioning in youth at clinical high risk for psychosis. (19th April 2017) - Velthorst, Eva; Zinberg, Jamie; Addington, Jean; Cadenhead, Kristin S.; Cannon, Tyrone D.; Carrión, Ricardo E.; Auther, Andrea; Cornblatt, Barbara A.; McGlashan, Thomas H.; Mathalon, Daniel H.; Perkins, Diana O.; Seidman, Larry J.; et al.
Abstract: The developmental course of daily functioning prior to first psychosis-onset remains poorly understood. This study explored age-related periods of change in social and role functioning. The longitudinal study included youth (aged 12–23, mean follow-up years = 1.19) at clinical high risk (CHR) for psychosis (converters [CHR-C], n = 83; nonconverters [CHR-NC], n = 275) and a healthy control group ( n = 164). Mixed-model analyses were performed to determine age-related differences in social and role functioning. We limited our analyses to functioning before psychosis conversion; thus, data of CHR-C participants gathered after psychosis onset were excluded. In controls, social and role functioning improved over time. From at least age 12, functioning in CHR was poorer than in controls, and this lag persisted over time. Between ages 15 and 18, social functioning in CHR-C stagnated and diverged from that of CHR-NC, who continued to improve ( p = .001). Subsequently, CHR-C lagged behind in improvement between ages 21 and 23, further distinguishing them from CHR-NC ( p < .001). A similar period of stagnation was apparent for role functioning, but to a lesser extent ( p = .007). The results remained consistent when we accounted for the time to conversion. Our findings suggest that CHR-C start lagging behind CHR-NC in social and role functioning in adolescence, followed by a period of further stagnation in adulthood.